Schooling in sex workers from San José, Costa Rica, at the beginning of the twenty-first century (UNED Research Journal, 2009)
Schooling in sex workers from San José, Costa Rica, at the beginning of the twenty-first century. San Jose is the capitol city of Costa Rica, a small Central American country characterized by a higher educational level, higher per capita income and higher living standards than the rest of the countries in the region. A study in 1975 indicated that female sex workers in the city were women who had chosen sex work because they earned much more than in other job options available to women who only had finished part of the primary school, and that nearly half did not want to change their activity. In order to know whether the situation had changed three decades later, in 2008 we interviewed 78 women who perform sex work in the city, with fares between US$3 and US$100 per hour and ages between 18 and 81 years. The interviews were based on a questionnaire; respondents were paid for their time, and data were analyzed with the SPSS statistical program. Most of these workers are Costa Ricans of urban origin, few have education beyond primary school, and they consider that the school years that they approved -despite receiving little help in this area from their families- are among their main achievements in life. One third of the women said that they had had a pleasant childhood, and most stated that they do not see a conflict between their work and religious beliefs because they provide sexual services to support their children (most are single mothers). Some believe that their work reduces sexual violence; most use condoms as protection and believe in the patriarchal view that women raise families while men provide resources. Universities could support these women with grants and advice; and finance more studies to separate myth from reality in this field, for example, with studies based on life histories, a technique that would give sex workers a voice from the conception of their own worlds and the environment in which they develop.
Keywords: Education; sex work; socialization; patriarchy; culture; prostitution.